2021
DOI: 10.1108/jadee-11-2017-0128
|View full text |Cite
|
Sign up to set email alerts
|

Shortage of pulses in India: understanding how markets incentivize supply response

Abstract: PurposeThis paper aims to understand the significant farm and market-level factors that incentivize the adoption and marketing of pulses influencing its supply response to changing demand.Design/methodology/approachThe authors first use a modified Nerlovian supply response model using secondary data to identify the major price and non-price factors influencing the supply of pigeon pea, black and green gram in the major pulses growing states in India. Second, using primary qualitative data the authors map the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The previous year's planted area had a significant effect on farmers' decisions to allocate more land for main-season rice (model 1) and less land for off-season rice (model 2). The results were justified in a past study where Abraham and Pingali [11] found that experience has a positive impact on the supply response of various crops in India.…”
Section: Long-run and Short-run Association Between Rice Supply And Relative Pricementioning
confidence: 62%
See 3 more Smart Citations
“…The previous year's planted area had a significant effect on farmers' decisions to allocate more land for main-season rice (model 1) and less land for off-season rice (model 2). The results were justified in a past study where Abraham and Pingali [11] found that experience has a positive impact on the supply response of various crops in India.…”
Section: Long-run and Short-run Association Between Rice Supply And Relative Pricementioning
confidence: 62%
“…The supply response of various crops is dominated by non-price factors over price factors. Non-price factors such as production area, access to irrigation and rainfall [11], agroclimatic risk [24], rice procurement [25], and poor price transmission and institutional problems of market access [26][27][28] rather than price factors is seen as having a significant influence on supply. Among others, seasonal fluctuation is the major and missed non-price factor that determines the supply response of various crops [28].…”
Section: Brief Literature Review On Supply Responsementioning
confidence: 99%
See 2 more Smart Citations
“…In the storage services, intermediaries form an important component in the provisions of storage facilities (Issa & Munishi, 2020;Yigzaw et al, 2016). Although the on-going discussion among scholars provide contradicting observations about the importance of intermediaries in business (Stewart, 2022;Abraham & Pingali, 2021;Pingali et al, 2019;Eberhart & Eeseley, 2018), in this context, intermediaries play a very critical role such as facilitating fruits and vegetables assembly and accumulation, providing preserving materials like non-human harmful insecticides as well as facilitating packaging and packing of fresh produces (Issa & Munishi, 2020;Sparks, 2013).…”
Section: Introductionmentioning
confidence: 99%